2015
DOI: 10.1093/jac/dkv306
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence ofSalmonellaand IMP-4-producing Enterobacteriaceae in the silver gull on Five Islands, Australia

Abstract: ObjectivesThe objective of this study was to investigate the silver gull as an indicator of environmental contamination by salmonellae and carbapenemase-producing Enterobacteriaceae (CPE) in south-east Australia.MethodsA total of 504 cloacal samples were collected from gull chicks at three nesting colonies in New South Wales, Australia [White Bay (n = 144), Five Islands (n = 200) and Montague Island (n = 160)] and were examined for salmonellae and CPE. Isolates were tested for carbapenemase genes and susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 31 publications
7
107
2
Order By: Relevance
“…These findings, in addition to previous reports from Australia (3,4,6), revealed that IncA/C 2 plasmids encoding IMP-like M␤Ls have played a major role in both human and animal societies, although with different dynamics. The broad-range characteristic of IncA/C plasmids, the rapid evolution of these molecules, and their role in the dissemination of multiple resistance genes, including bla CMY , bla NDM , bla VIM , and bla IMP , underscore the increasing clinical importance of this plasmid family, as well as the spreading potential of large multidrug resistance segments through reshuffling of enterobacterial plasmids by homologous recombination.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…These findings, in addition to previous reports from Australia (3,4,6), revealed that IncA/C 2 plasmids encoding IMP-like M␤Ls have played a major role in both human and animal societies, although with different dynamics. The broad-range characteristic of IncA/C plasmids, the rapid evolution of these molecules, and their role in the dissemination of multiple resistance genes, including bla CMY , bla NDM , bla VIM , and bla IMP , underscore the increasing clinical importance of this plasmid family, as well as the spreading potential of large multidrug resistance segments through reshuffling of enterobacterial plasmids by homologous recombination.…”
Section: Resultssupporting
confidence: 65%
“…In a previous study from our group, IncA/C plasmids carrying bla IMP genes were identified in Enterobacteriaceae isolates recovered from cloacal samples that were collected from gull chicks at a nesting colony in New South Wales, Australia (6). These plasmids were mainly associated with the integron In809 (7), whose variable region comprised the bla , qacG, aacA4, and catB3 cassettes.…”
mentioning
confidence: 98%
“…An E. coli CMUL 64 specimen isolated from domesticated chickens in Lebanon in December 2013 contained bla OXA-48 in addition to two ESBLs [Al Bayssari 2015]. Surveillance of Silver Gull ( Chroicocephalus novaehollandiae ) excrement from South-East Australia in October 2012 found that CPE carriage was alarmingly high (71.8%, 120/167) and almost completely due to bla IMP-4 (96.7%, 116/120), but bla IMP-26 (1.67%, 2/120) and bla IMP-38 (5.83%, 7/120; 5/7 in E. coli ST58 co-producing bla IMP-4 ) were also detected [Dolejska 2016]. This agrees with clinical observations reporting bla IMP-4 as the most prevalent gene from CPE clinical isolates in Australia, indicating either high transmission frequency of bla IMP-4 to human pathogens or that these CPE environmental isolates can be infectious agents [Dolejska 2016].…”
Section: Non-infectious Surveillancementioning
confidence: 99%
“…Unlike bla in Pseudomonas aeruginosa, which was described at the same time and place and found to be on a narrowhost-range IncP2 plasmid of Pseudomonas (3,29), bla IMP-4 has been observed to spread to a variety of Gram-negative species, plasmid incompatibility groups, and genetic contexts in clinical, animal, and environmental isolates in the last 15 years (10,(30)(31)(32)(33). bla IMP-4 is most commonly carried on IncL/M and IncA/C2 plasmids (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2B), typically in the cassette array bla IMP-4 -qacG2-aacA4-catB3 in a class 1 integron (10,34). This cassette array was described in Acinetobacter baumannii from a Hong Kong outbreak (7,8) and from Singapore (11), K. pneumoniae pIMP-PH114 from Hong Kong (35), Enterobacter cloacae from Australia (32), K. pneumoniae pJIBE401 (10), E. cloacae plasmid pEl1573 (34), and Enterobacteriaceae in silver gulls in Australia (33), where the bla IMP-4 cassette is in a sul1-type class 1 integron (i.e., with a 3=-CS). Additionally, there is a sul1-type class 1 integron from a K. pneumoniae isolated from Shanghai that has a single bla cassette with a group II intron in its attC site (36).…”
Section: Discussionmentioning
confidence: 99%